New wheat storage structures and their effects on grain quality in Sindh, Pakistan - Chattha, Shakeel Hussain (2015)
A considerable quantum of grains is deteriorated during storage due to several defects in the storage structures. The present study was conducted considering the problems with regard to wheat losses during storage. Thus, a survey was conducted to identify wheat storage methods and associated problems. This followed a practical evaluation of traditional or existing wheat storage structures using Complete Randomized Design (CRD). Three new structures were also developed to cope up with the existing storage problems. These developed structures were tested in-situ under CRD. This study was conducted in four major wheat growing districts of Sindh province namely, Hyderabad,Sukkur, Badin and Shaheed Benazir Abad. The average area of land in the studied districts under wheat crop was 5 acres and the average total production of wheat was 6500 kg out of which 2500 kg of wheat was available for storage by farmers for seed,home consumption and sell to the market. Wheat storage structures which were found to be used by farmers of study areas included: earthen bin (23%), metallic bin (16%),bamboo/straw bin (20%), bulk covered (17%), bags covered (10%) and room type structures (14%). The survey results revealed that the traditional structures were not an insect, rodent, fungi and moisture proof. Traditional structures were found to have various defects such as cracks, holes, leakages and structural failure in the roof, walls and floor of the structures because of poor strength of materials and improper design of structures. Other storage problems were loss of seed germination capacity,discoloration of the grain, and sprouting during storage. Based on the results of the study, the above mentioned problems incur about 10 to 40% of the stored wheat grain loss annually. During the practical evaluation, wheat grain stored in these structures was sampled from July 2013 to July 2014 at 3 months interval and was analyzed for quality deterioration over time and space. This means, the effect of structure, time and location were observed. The highest values of grain temperature (36.08 °C), insectinfestation (12.55%), weight loss (1.65%), fungal incidence (17.25%) and aflatoxin level (8.35 μg kg-1) were observed in grains stored in room store, followed by bags covered, bamboo/straw bin, bulk covered method, metal bin and then earthen bin. Deterioration of grain quality showed an increasing pattern with prolonged storage in traditional structures. The maximum deterioration with respect to location of wheat grain was noted for district Badin followed by Sukkur, Shaheed Benazir Abad and Hyderabad. Thus, the pests that infested wheat stored in these storage methods were not only contaminating the stored wheat, but also consumed the nutrients of the wheat for their development and proliferation thereby leading to the farmer‟s food insecurity. Three different types of storage bins (concrete block bin, ferrocement bin and strawclay bin) of similar dimensions were designed and constructed to solve the grain storage problems. The constructed bins have several advantages such as ease of loading and unloading of grain, capable of bearing the desired load, insect and rodent proof,prevention of temperature and moisture variation, and allow pest control practices over traditional storage structures. Wheat samples were also taken from these bins at 3 months interval from July 2013 to July 2014 to assess the efficiency of bins in retaining the quality and quantity of wheat grains stored at 2 different initial moisture levels (11 and 15%). Storage period greatly affected the quality of stored grains. The maximum values of germination capacity (89.5%), 1000 grain weight (44.03 g), test weight (72.14 kg hl-1), flour yield (64.88%), starch (65.33%), protein (12.25%), dry-gluten (9.31%), fat (2.77%), ash (1.91%), falling number (301.6 sec), water absorption (66.52%), dough development time (6.23 min) and dough stability (9.31 min) were detected from grain stored in straw-clay bin followed by the concrete block bin and then ferrocement bin. However, grain moisture contents at loading (11 and 15%) showed very little effect on the quality characteristics of wheat grain. The developed storage bins have proven to be a promising solution to reduce storage losses by almost more than half of existing losses and preserve quality of wheat grain. Based on the good performance of newly developed structures, it is recommended that the existing structures should be replaced with these newly developed structures in accordance with the farmers‟ financial condition. This replacement will reduce the wheat grain loss on one hand and on the other it will prosper the farmer in particular and flourish the national economy in general.